Kema’mulan Hadis Ahad Yang Ta’arudh dengan Qiyas dan Pengaruhnya terhadap Eksistensi Dalil Hukum - Suhefri, Suhefri (Universitas Islam Negeri Imam Bonjol Padang, 2013)
If in case a proposition requires the enactment of the law on a case, but there is also another proposition which requires the enactment of another law on the same case, the second argument of the so-called ta'arudh. Clash between the two arguments of the law could include naqli proposition (proposition textually defined in the Qur'an or Hadith), and the argument of aqli (determined based on reasonable arguments). In addition it can also include the definitive proposition (proposition that power in applying the laws, convincing), and the argument of zhanni (proposition that power in applying the laws are not convincing). One form ta'arudh it happen between tradition Munday with qiyas. When that happens, where would serve as proof of the basis for the charity? Regarding the problem is exactly what will be discussed in this paper is very simple.